2023
DOI: 10.1136/bmjopen-2023-073188
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of intermittent blood flow restriction training and high-load resistance training in patients with patellofemoral pain: study protocol for a randomised trial

Weiya Kong,
Haonan Wang,
Lin Cheng
et al.

Abstract: BackgroundPatellofemoral pain (PFP) syndrome is a common knee joint functional disorder. Blood flow restriction (BFR) training has shown promise in improving PFP; however, the effectiveness of intermittent BFR (iBFR) training remains uncertain. This study aims to compare the rehabilitative effects of iBFR combined with low-load resistance training and high-load resistance training in PFP patients and to assess the effectiveness of iBFR combined with low-load resistance training for improving PFP.Methods and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Typically, patellofemoral pain is caused by altered stress on the patellofemoral joint from intrinsic knee factors, alterations in the kinetic chain, or errors in training [ 5 ]. Existing research has demonstrated a strong correlation between PFP and deficits in quadriceps and hip abduction strength [ 6 , 7 ]. Insufficient hip abduction muscle strength can lead to functional impairment of lower limb joint alignment, increasing patellofemoral joint stress and thereby elevating the risk of injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, patellofemoral pain is caused by altered stress on the patellofemoral joint from intrinsic knee factors, alterations in the kinetic chain, or errors in training [ 5 ]. Existing research has demonstrated a strong correlation between PFP and deficits in quadriceps and hip abduction strength [ 6 , 7 ]. Insufficient hip abduction muscle strength can lead to functional impairment of lower limb joint alignment, increasing patellofemoral joint stress and thereby elevating the risk of injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%